The Impact of Spirituality on Alcoholics in Select De-Addiction Centres in Tiruchirappalli District, Tamilnadu - Prof. Vinothkumar. J; Dr. Andrew. F (International Journal of Engineering and Management Research, 2019)
Aim: The aim of the study was to examine the individual prayer involvement, church/temple and mosque attendance and involvement in pilgrimage among the in-patients of alcohol de-addiction centre. Method: The sample consisted of 118 patients. The age range of the sample between 23 and 64 years. The tools used in the study were personal information data sheet, individual prayer involvement, church/temple and mosque attendance and involvement in pilgrimage questionnaire. The data were analysed using percentage analysis independent, cross tabulation and one-way ANOVA through IBM SPSS 20. Results: From the output of Reliability Statistics obtained Cronbach's Alpha value of 0.707 > 0.600. On the basis of decision-making in the reliability test, we could be found that this research questionnaire is reliable, where as it is a high level of reliability. 87 of the respondents are married, 30 percent of the respondents are drink 465 ml of alcohol per day and 23 percent drink 750 ml of alcohol per day. In overall out of 118 respondents 57.6% of the respondents are worship their gods, 14.4% are spent more time with their family members, 11% are doing yoga and meditation, 7.6% are spent more time with nonalcoholic friends and 4.2% are admit themselves into hospital/de addiction centres to get rid of alcoholism. From the one way ANOVA table it can be observed that the mean value on the study dimensions are Christian respondents (M=2.7586), the Muslim respondents (M=2.7368) and the Hindus (M=2.2571). Conclusion: The results were revealed the majority of the respondents first drinking age below twenty years. Nearly half of the respondents are already taken the treatment and now relapsed. There is a significance difference between Age and Individual prayer, Church involvement and involvement in pilgrimage of the respondents. There is no significant difference between the Individual Prayer between the Prefer to Drink Alcohol, involvement in church / temple / mosque between the Prefer to Drink Alcohol and the time of pilgrimage between the Prefer to Drink Alcohol.